The Moderating Impact of Market Power on The Relationship Between Market Share and Banking Profitability - Aziz, Lukmanul Hakim; Siregar, Hermanto; Achsani, Noer Azam; Irawan, Tony (Journal of Ecohumanism, 2024)
This study aims to determine the relationship between market power, market share, and profitability, all extremely useful to strengthen the Early Warning System (EWS), in maintaining the stability of the Indonesian Banking System, especially among the Regional Development Banks (BPD). Utilizing SCP-ESH as the principle, analysis was conducted using quarterly financial reports from 24 Indonesian Regional Development Banks over the period of ten years, from 2012 to 2022. Regression analysis from static panel data found that market power directly impacted Return on Assets (ROA) positively while market share had a negative impact. However, when the interaction between these two factors was factored in, they affected the ROA number positively. Control variables such as technical efficiency, fee-based income, and liquidity ratio at the regional level had a positive impact on ROA, while factors such as interest rate spread, capital adequacy ratio, bank overheads, and non-performing loans had a negative impact. Overall, market-power was shown to synergize positively with these control variables.